HEPATOPROTECTIVE PROPERTIES OF LOW MOLECULAR WEIGHT CHITOSAN - Zulfiya I. Galieva; Firuza Kh. Inoyatova; Vazira Rakhmanova; Sayora Sh. Rashidova (Central Asian Journal of Medicine, 2024)
In 30 rats with acute toxic liver damage caused by the administration of CCl4 in olive oil over a span of four days, at a dosage of 2.5 milligrams per kilogram of body weight, biochemical indicators of liver damage were studied. To reproduce acute toxic liver damage, 30 rats were administered CCI4 4 times at a dose of 2.5 ml/kg body weight subcutaneously for 4 days. No mortality was observed. Pharmacotherapy of acute toxic liver damage was carried out 24 hours after the final administration of the toxicant. The animals were separated into the following groups: control group (10 rats) with ATH + placebo (H2O); comparison group (10 rats) with ATH + comparison drug Carsil at a dose of 100 mg/kg; main group (10 rats) with ATH + LMWC at a dose of 25 mg/kg. The drugs were administered as a suspension intragastrically through a special tube for 12 days. In the control group, the development of syndromes of cytolysis, cholestasis, mesenchymal inflammation, and hepatic cell failure, a decrease in catalase activity, and an elevation in the content of MDA, FASL, and NF-kB was established, which coincided with the morphological signs of hepatocyte destruction. Low-molecular chitosan obtained from Bombyx mori pupae to a certain extent restored the histiostructure of the liver of rats with ATH, reduced the processes of lipid peroxidation and apoptosis, cytolysis, cholestasis and hepatocellular failure. In terms of hepatoprotective action, it was not inferior to the classical hepatoprotector Carsil.